2020
DOI: 10.1177/2050640620939788
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal bleeding in patients with pancreatic cancer: Causes and haemostatic treatments

Abstract: Background Gastrointestinal bleeding is a rare but severe complication of pancreatic ductal adenocarcinoma. Objective The purpose of this study was to describe the causes and treatments of non-postoperative gastrointestinal bleeding in patients with pancreatic ductal adenocarcinoma, and explore the parameters associated with therapeutic effectiveness. Methods Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…In our present study, hemostasis was achieved in 14 out of 20 patients (70%), which was consistent with previous reports of rates ranging from 54-73% from studies conducted in gastric cancer patients [13,[15][16][17]. Aguilera ML et al, who performed a comprehensive study of the causes and treatments of GIB in PC patients, reported that PRT was associated with a hemostasis rate of 100% (8/8) [4]. However, in their study, hemostasis was de ned solely on the basis of the reduced volume of RBC transfusion needed after PRT as compared with that before PRT.…”
Section: Discussionsupporting
confidence: 92%
“…In our present study, hemostasis was achieved in 14 out of 20 patients (70%), which was consistent with previous reports of rates ranging from 54-73% from studies conducted in gastric cancer patients [13,[15][16][17]. Aguilera ML et al, who performed a comprehensive study of the causes and treatments of GIB in PC patients, reported that PRT was associated with a hemostasis rate of 100% (8/8) [4]. However, in their study, hemostasis was de ned solely on the basis of the reduced volume of RBC transfusion needed after PRT as compared with that before PRT.…”
Section: Discussionsupporting
confidence: 92%
“…A study has shown that radiation therapy in comparison with endoscopic treatment caused less recurrence and higher immediate efficacy in hemostasis in patients with GI bleeding due to gastric invasion of pancreatic cancer. 10 Our patient had complete cessation of bleeding with palliative radiotherapy but unfortunately died of complications of the progressive disease. More knowledge on PASC including appropriate treatment strategies and different forms of clinical presentations is still needed to increase the rate of overall patient survival.…”
Section: Discussionmentioning
confidence: 68%
“…8 In patients with pancreatic cancer, the risk of gastrointestinal bleeding may be higher when the tumor invades the gastrointestinal tract. 15 In our study, tumor invasion to the gastrointestinal tract was observed in both patients with pancreatic cancer and gastrointestinal bleeding. From the data in clinical trials and our study, rivaroxaban was associated with higher major bleeding risk in patients with gastrointestinal cancer and pancreatic cancer, so the use of rivaroxaban in this population should be cautious.…”
Section: Discussionmentioning
confidence: 50%